Implemetasi Teori Motivasi Abraham Maslow dalam Pembelajaran Pendidikan Agama Islam - Ningtyas, Dea Tara; Farida, Nur Aini; Firadilah, Ais (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2022)
The success of Islamic religious learning is based on achievements that are prioritizing character-building aspects, conscience, and concern for social phenomena in society. In order to achieve them, teachers must emphasize the students' learning motivation and engagement in the learning process by employing a humanist approach to learning. One of these approaches was initiated by Abraham Maslow in the form of a motivation theory or a theory centered on meeting student needs. This study aimed to describe the implementation of Abraham Maslow's motivation theory in Islamic religious learning. This qualitative study employed field research which collected data from direct interviews with Islamic religious teachers and seventh-grade students, and essential data relating to the variables studied from observation and documentation. The analysis used in this research was the phenomenology approach and the text related to it. Based on the findings, it was stated that the implementation of Abraham Maslow's motivation theory has been fully implemented. These needs were the fulfillment of physiological needs; fulfillment of security needs, love and affection needs, social needs, and self-actualization needs. By fulfilling these needs, students not only acquire good learning outcomes but also can develop their potential in other fields well.